Academic Supervision, Work Motivation, and Collaborative Learning Practices in Enhancing Teacher Performance at Public Senior High Schools in Berau Regency - Sitorus, ellen; Haeruddin, Haeruddin (Borneo Educational Journal (Borju), 2025)
This comprehensive study examines the influence of academic supervision, work motivation, and collaborative learning practices on teacher performance in three public senior high schools in Berau Regency. Using a quantitative approach with cluster random sampling, the research involved 159 teachers from three accredited "A" schools out of a total population of 280 teachers across five schools. Data collection was carried out through validated and reliable questionnaires, and the data were analyzed using multiple linear regression techniques.      The results reveal that academic supervision significantly affects teacher performance, accounting for 35% of the variance, with work motivation contributing an additional 6.9%. Similarly, collaborative learning practices exert an influence comparable to that of academic supervision, also at 35%. Collectively, these factors explain 35% of the variability in teacher performance, with the remaining influence attributed to other unmeasured factors.   This study underscores the importance of a synergistic approach, where academic supervision provides constructive feedback, incentives motivate teachers, and collaborative learning fosters ongoing professional development. Recommendations include enhancing academic supervision through targeted training for school principals, implementing performance-based rewards by local governments, and establishing sustainable collaborative learning programs within schools to promote innovation and continuous improvement in teaching practices. The findings serve as valuable input for educational policymakers in Berau Regency and contribute to the broader goal of elevating the quality of education in Indonesia. The research highlights the critical role of effective supervision, motivation, and collaborative practices in fostering high-performing teachers and improving educational outcomes